2018
DOI: 10.1029/2018ja025205
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Correlation Analysis of Field‐Aligned Currents Measured by Swarm

Abstract: We investigate the statistical, dual-spacecraft correlations of field-aligned current (FAC) signatures between two Swarm spacecraft. For the first time, we infer the orientations of the current sheets of FACs by directly using the maximum correlations obtained from sliding data segments. The current sheet orientations are shown to broadly follow the mean shape of the auroral boundary for the lower latitudes and that these are most well ordered on the dusk side. Orientations at higher latitudes are less well or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
2
6
0
Order By: Relevance
“…In our view, this is significant since it validates the electrodynamic importance of the regions between adjacent oppositely directed currents for electromagnetic energy transport from the magnetosphere to the ionosphere. Similar scale-dependent separation between temporally varying wave-like dynamics (~10s km) and more static FACs (>50 km) using Swarm magnetic field cross correlations using mostly Swarm A and C at was also reported by Yang et al (2018). The three Alfvén speeds correspond to the maximum, mean, and minimum Alfvén speeds determined during the crossing period (calculated using Swarm C density measurements since Swarm A density measurements were unavailable for this time period).…”
Section: 1029/2019ja027277supporting
confidence: 76%
“…In our view, this is significant since it validates the electrodynamic importance of the regions between adjacent oppositely directed currents for electromagnetic energy transport from the magnetosphere to the ionosphere. Similar scale-dependent separation between temporally varying wave-like dynamics (~10s km) and more static FACs (>50 km) using Swarm magnetic field cross correlations using mostly Swarm A and C at was also reported by Yang et al (2018). The three Alfvén speeds correspond to the maximum, mean, and minimum Alfvén speeds determined during the crossing period (calculated using Swarm C density measurements since Swarm A density measurements were unavailable for this time period).…”
Section: 1029/2019ja027277supporting
confidence: 76%
“…A complementary technique based on the cross-correlation of the single spacecraft estimates of FACs at each Swarm spacecraft has been recently introduced (Lühr et al 2015;Yang et al 2018), which results in estimates of the maximum correlation between sliding data intervals at two-spacecraft. The position of the maximum correlations found can be defined in terms of the required time shift (for example, from spacecraft A-C) and corresponding difference in the local time (this is given by the relative location of the spacecraft on the pair of orbits), and the correlation values can be computed as a function of local time (MLT) of the orbits.…”
Section: Current Sheet Orientation Implied By 2-spacecraft Correlationsmentioning
confidence: 99%
“…Conversely, if there are significant small-scale structures or fluctuations present then this will be reflected in unstable orientations and a lack of ordering. Figure 5.9 (adapted from Yang et al 2018) shows the patterns in current sheet orientations found for intervals broadly associated with both region 1 and region 2 currents. Yang et al (2018), for a Northern hemisphere polar map, showing the average FACs for Swarm A and C data from 17th Apr.…”
Section: Current Sheet Orientation Implied By 2-spacecraft Correlationsmentioning
confidence: 99%
“…During times where both SWARM satellites are operational and cross a stable arc, their measurements can give us an example to validate our conjecture. The SWARM spacecraft are displaced in both time and space from one another and as long as the arc is stable over the period of time between the spacecraft crossings we can compare the data (Yang et al, ).…”
Section: In Situ Verification Of Arc Boundary Perturbationmentioning
confidence: 99%
“…In the long run, successful interpretation of image events without the need for in situ measurements can then be applied for events outside the rocket flight, where only ground‐based measurements are present, in order to interpret the fields around auroral arc boundaries, with similar improvement over previous radar data maps not utilizing camera imagery. We show examples utilizing data outside our rocket flight from the SWARM satellites (Yang et al, ) and PFISR data products (Heinselman & Nicolls, ) in section .…”
Section: Introductionmentioning
confidence: 99%